Computer Vision for Jaundice - KHUDHUR, ZAINAB KHALEEL; Ahmad, Tiba Muhammad; Taha, Noor Mahmoud (American Journal of Biodiversity, 2025)
Physiological jaundice occurs in the first week of life in newborns due to the increase in bilirubin level which leads to yellowish discoloration of skin and sclera. Sever jaundice and toxic level of bilirubin can cause brain damage as bilirubin exists in the central nervous systems. Invasive detection can cause blood loss and leads to anemia, especially when repeated blood tests are required. Blood tests put the infant at risk of infection. The proposed system uses the mobile camera as a color-based screening tool because it is affordable, objective, ubiquitous, and less painful for infants. Based on the color analysis obtained from the captured images, jaundice was detected.